Ca2+/calmodulin‐dependent protein kinase II‐γ (CaMKIIγ) negatively regulates vascular smooth muscle cell proliferation and vascular remodeling. Issue 3 (13th November 2015) - Saddouk, Fatima Z.; Sun, Li‐Yan; Liu, Yong Feng; Jiang, Miao; Singer, Diane V.; Backs, Johannes; Van Riper, Dee; Ginnan, Roman; Schwarz, John J.; Singer, Harold A.
Abstract : Vascular smooth muscle (VSM) expresses calcium/calmodulin‐dependent protein kinase II (CaMKII)‐δ and ‐γ isoforms. CaMKIIδ promotes VSM proliferation and vascular remodeling. We tested CaMKIIγ function in vascular remodeling after injury. CaMKIIγ protein decreased 90% 14 d after balloon injury in rat carotid artery. Intraluminal transduction of adenovirus encoding CaMKIIγC rescued expression to 35% of uninjured controls, inhibited neointima formation (>70%), inhibited VSM proliferation (>60%), and increased expression of the cell‐cycle inhibitor p21 (>2‐fold). Comparable doses of CaMKIIδ2 adenovirus had no effect. Similar dynamics in CaMKIIγ mRNA and protein expression were observed in ligated mouse carotid arteries, correlating closely with expression of VSM differentiation markers. Targeted deletion of CaMKIIγ in smooth muscle resulted in a 20‐fold increase in neointimal area, with a 3‐fold increase in the cell proliferation index, no change in apoptosis, and a 60% decrease in p21 expression. In cultured VSM, CaMKIIγ overexpression induced p53 mRNA (1.7 fold) and protein (1.8‐fold) expression; induced the p53 target gene p21 (3‐fold); decreased VSM cell proliferation (>50%); and had no effect on expression of apoptosis markers. We conclude that regulated CaMKII isoform composition is an important determinant of the injury‐induced vasculoproliferative response and that CaMKIIγ and ‐δ isoforms have non‐equivalent, opposing functions.—Saddouk, F. Z., Sun, L.‐Y., Liu, Y. F., Jiang, M., Singer, D. V., Backs, J., Van Riper, D., Ginnan, R., Schwarz, J. J., Singer, H. A., Ca2+/calmodulin‐dependent protein kinase II‐γ (CaMKIIγ) negatively regulates vascular smooth muscle cell proliferation and vascular remodeling. FASEB J. 30, 1051–1064 (2016). www.fasebj.org